PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), KEKUASAAN DIREKSI, DAN PENGUNGKAPAN GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Nurul Aulia Rohmah; R. R. Sri Handayani (Diponegoro Journal of Accounting, 2026)
This study aims to test the effect of Corporate Social disclosure, executive power, and Good Corporate Governance disclosure on earnings management in Transportation and Logistics sector companies listed on the Indonesia Stock Exchange from 2021 to 2025.This study uses secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) and the respective official websites of Transportation and Logistics sector companies for the 2021-2025 period. Sampling was conducted using a convenience sampling method based on data availability and completeness throughout the observation period, resulting in a final sample of 139 observations over the 5-year research period. The analysis method employed in this research is Multiple Linear Regression Analysis.The results of this study indicate that Corporate Social Responsibility disclosure has no effect on earnings management, while executive power has a negative effect on earnings management. Furthermore, Good Corporate Governance disclosure does not prove to have an effect on earnings management.